2021
DOI: 10.1111/ijd.15938
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in a cohort of patients with moderate‐to‐severe atopic dermatitis. Influence of dupilumab treatment

Abstract: Introduction Atopic dermatitis is a systemic and immune-mediated dermatological disease that comprises a wide group of physiological and psychological comorbidities. Within the latter, the evaluation of anxiety and depression has been the subject of numerous studies, but sexual dysfunction (SD) is a fact that is rarely addressed in the literature. The objective of the present study is to assess the prevalence of SD in a cohort of patients with moderate-to-severe atopic dermatitis (AD) and to establish the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A few studies have addressed the sexual life of patients with AD, but most of them have focused mainly on male sex ( 18 , 23 , 24 ). One Dutch study with a small sample size found that sexual satisfaction and self-perception of appearance in women with AD is significantly lower than in general populations.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have addressed the sexual life of patients with AD, but most of them have focused mainly on male sex ( 18 , 23 , 24 ). One Dutch study with a small sample size found that sexual satisfaction and self-perception of appearance in women with AD is significantly lower than in general populations.…”
Section: Discussionmentioning
confidence: 99%
“…In the questionnaire applied, one of the main topics we may highlight is the fact that AD affects the sexual life of women of childbearing age [ 13 , 14 ]. The sexual life of patients with atopic dermatitis of longer evolution (>13 years) is significantly affected compared to patients with less evolution in time (<13 years) (6.00 ± 2.42 vs. 7.32 ± 2.80; p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Sexual health impairment has not been consistently assessed in patients with AD, despite the societal and personal importance of sex and its key role within patient-reported outcomes and impact on QoL [1,5,6]. It has been observed that AD patients are more likely to report sexual dysfunction than healthy controls [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The convergence of a proinflammatory state, abnormal hormonal levels and the psychological impact of eczema on genital areas might explain the high levels of sexual dysfunction reported by male and 2 of 10 female patients with AD [9,10]. Nevertheless, to date, only one report has evaluated the impact of an adequate treatment on sexual dysfunction in patients with AD [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation